Aggregate Behavior and Microdata - Werner Hildenbrand; Alois Kneip (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
It is shown how one can effectively use microdata in modelling the change over time in an aggregate (e.g. mean consumption expenditure) of a large and heterogeneous population. The starting point of our aggregation analysis is a specification of explanatory variables on the micro-level. Typically, some of these explanatory variables are observable and others are unobservable. Based on certain hypotheses on the evolution over time of the joint distributions across the population of these explanatory variables we derive a decomposition of the change in the aggregate which allows a partial analysis: to isolate and to quantify the effect of a change in the observable explanatory variables. This analysis does not require an explicit treatment of the unobservable variables.
Keywords: E21; D12; 330; Verbraucherausgaben; Aggregation; Gesamtwirtschaftlicher Konsum; Mikrozensus; Zeitreihenanalyse; Schätzung; Theorie; Grossbritannien; Mikrodaten